Psalm 54: The power of positive patterning - Botha, P. J. (Verbum et ecclesia, 2000)
Psalm 54: The power of positive patterning Psalm 54 is analysed in 'n literary, rhetorical and socio-critical way in order to determine the dominant textual strategy and the way in which it was supposed to function. It is established that the basic concern of the psalm is with the honour of the individuals for whom the psalm was intended as a cultic prayer. The way in which words with a positive and those with a negative connotative meaning are arranged, is found to be compliant with the purpose of having the enemies exposed and the self vindicated. What is more, this pattern seems to have been devised also to be of therapeutic value for the suppliant himself.